Transfer of radiocesium to four cruciferous vegetables as influenced by organic amendment under different field conditions in Fukushima Prefecture. (February 2015) - Aung, Han Phyo; Djedidi, Salem; Yokoyama, Tadashi; Suzuki, Sohzoh; Bellingrath-Kimura, Sonoko Dorothea
Abstract: Soil-to-plant transfer of radiocesium ( 137 Cs) in four cruciferous vegetables as influenced by cattle manure-based compost amendment was investigated. Komatsuna, mustard, radish and turnip were cultivated in three different 137 Cs-contaminated fields at Nihonmatsu City in Fukushima Prefecture from June to August 2012. Results revealed that organic compost amendments stimulated plant biomass production and tended to induce higher 137 Cs concentration in the cruciferous vegetables in most cases. Among the studied sites, Takanishi soil possessing low exchangeable potassium (0.10 cmolc kg −1 ) was associated with an increased concentration of 137 Cs in plants. Radiocesium transfer factor (TF) values of the vegetables ranged from 0.025 to 0.119. The increase in 137 Cs TFs was dependent on larger plant biomass production, high organic matter content, and high sand content in the studied soils. Average 137 Cs TF values for all study sites and compost treatments were higher in Komatsuna (0.072) and radish (0.059), which exhibited a higher biomass production compared to mustard and turnip. The transferability of 137 Cs to vegetables from soils was in the order Komatsuna > radish > mustard > turnip. The highest 137 Cs TF value (0.071) of all vegetables was recorded for a field where the soil had high organic matter content and a high clay proportion of 470 g kg −1 consisting of Al-vermiculite clay mineral. Highlights: Komatsuna and radish possessing higher biomass resulted in higher 137 Cs TF than mustard and turnip. Soil with low exchangeable K (0.10 cmolc kg −1 ) increased 137 Cs concentration in plants. Compost amendments tended to induce higher 137 Cs transfer from soil to plants than the control. Soil with Al-vermiculite mineral and high organic matter resulted in higher 137 Cs transfer.